Efficacy and safety of danshen class injections in the treatment of coronary heart disease: a network meta-analysis - Shuang Dai; Yukun Ding; Jianbo Guo; Xian Wang (Frontiers in Pharmacology)
BackgroundDanshen [Salvia miltiorrhiza Bunge (Lamiaceae; Salviae miltiorrhizae radix et rhizoma)] class injections (DSCIs) are widely used in the treatment of coronary heart disease (CHD). However, there are various types of DSCIs available on the market, and it remains uncertain which DSCI has the best clinical efficacy, as well as which one is most effective in regulating inflammatory markers and oxidative stress indicators. The aim of this network meta-analysis (NMA) is to compare the therapeutic effects of different DSCIs to identify the optimal DSCI for the treatment of CHD.MethodsThe databases searched to identify randomized controlled trials (RCTs) of DSCIs for CHD included the China National Knowledge Infrastructure (CNKI), Wanfang Database, China Science and Technology Journal Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, Web of Science, and Cochrane Library. The search period spanned from the inception of each database up to June 2024. NMA was conducted using RevMan 5.3 and Stata 16.0 software.ResultsA total of 106 studies including 14,979 patients, involving 10,931 patients, with 5,640 in the experimental group and 5,291 in the control group. And ten DSCIs were extracted, namely: Danhong injection (DH), Danshen injection (DS), Danshenchuanxiongqin injection (DSCXQ), Dansenduofensuanyan injection (DSDFSY), Danshenfen injection (DSFZ), Fufang Danshen injection (FFDS), Guanxinning injection (GXN), Sodium Tanshinone IIA Sulfonate injection (STS), Xiangdan injection (XD), Shenxiongputaotang injection (SXPTT). The results of NMA showed that, XD injection significantly enhances clinical efficacy; STS is more effective in reducing hs-CRP levels; DSDFSY shows better efficacy in decreasing IL-1 and increasing NO levels; DSCXQ has a greater advantage in reducing IL-6 levels; GXN is more effective in regulating SOD levels; and DH is better at reducing MDA levels.ConclusionThe combined treatment of DSCIs and WM more significant efficacy in patients with CHD compared to WM treatment alone, including clinical efficacy evaluation, inflammatory markers, and oxidative stress markers. Overall, DSDFSY and DSCXQ show better performance in clinical efficacy evaluation and regulation of inflammatory markers, while DH exhibits a more stable effect in regulating oxidative stress. However, larger sample sizes and high-quality RCTs are still necessary to further compare the various DSCIs.Systematic Review Registration[PROSPERO], identifier [CRD42024548928].